Aislamiento y caracterización genética de levaduras marinas y su uso en camarones litopenaeus vannamei - Gabela Aguilar, Juan Enrique (2005)
The Ecuadorian and worldwide shrimp farming sector has been plagued with diseases of diverse origin. The lost incurred by these diseases are in the order of USD 100 million; hence a way to counteract them is necessary. The main source to minimize the impact of the diseases in the aquaculture sector has been the use of antibiotics, however, the problems that might arise with their use are well known, that is why, the current approach is the use of probiotics, among them the yeasts. The name “yeasts” are part of a group of microorganisms belonging to the genus Ascomycetes and Basidiomycetes, being able to be found in different habitats like: water, soil, organic matter, or in a symbiosis with other organisms. The results of this research show that is easy to isolate and produce alloctonous microorganisms (yeasts) from the sector already adapted to the local environmental conditions; that the genetic profile of the isolated lines after underwent a nested-PCR are Saccharomyces cerevisiae; and that the selected lines (29, 57, 39 and 36) showed a significant statistical difference (P < 0.01) when compared to a control in the NBT test, being the line 39 the one that showed the higher immunostimulating potential.